Spectrum of mutations of cystic fibrosis in the 22 Arab countries: A systematic review. Issue 2 (12th November 2018) - Al‐Sadeq, Duaa; Abunada, Taghreed; Dalloul, Rajaa; Fahad, Sara; Taleb, Sara; Aljassim, Kholoud; Al Hamed, Fatima Alzahra; Zayed, Hatem
ABSTRACT: Cystic fibrosis (CF) is an autosomal recessive genetic disease caused by mutations in the CFTR gene, with various clinical manifestations that affect pulmonary, digestive, exocrine and male reproductive functions as well as the bones and kidneys. This study aimed to reveal the spectrum of CFTR gene mutations in Arab CF patients and their corresponding clinical phenotypes among the 22 Arab countries. We searched four literature databases (PubMed, Science Direct, Web of Science and Scopus) from their times of inception to January 2018. All possible search terms were used to encompass the different clinical phenotypes, disease incidences, CFTR mutations, ages and consanguinity rates of CF patients in the 22 Arab countries. Our search strategy identified 678 articles; of these, 72 were eligible for this systematic review. We retrieved data from 18 Arab countries; only 1766 Arab patients with CF were identified, even after additional searches using Google and Google Scholar. The search uncovered a wide spectrum of mutations, some of which are shared with other ethnic groups and some unique to Arab patients. Although the clinical phenotypes of Arab patients were typical of CF, several distinct phenotypes were reported. Despite the rarity of genetic epidemiological studies of CF patients among the 22 Arab nations, the disease is frequently reported in Arab countries where consanguineous marriage is common. Therefore, significant attention should be paid to this problem by implementing carrier and premarital screening, newborn screening and genetic counselling. Abstract : See related Editorial